Medicinal use of plants by the peasant community of san jacinto, northern colombia (1999)
I studied the medicinal use of plants by the peasant community of the town of San Jacinto, located in the savanna of Bolívar, northern Colombia. Fifty-five families, 138 genera, and 118 species were scientifically identified from 249 specimens collected of the modern-day vegetation of San Jacinto. From these, 198 uses were recorded for 190 (76%) of the specimens. The 54 uses recorded for human medicine (27%) and the five uses recorded for animal medicine (2%) are discussed. Vernacular names, parts used, method of preparation, and medicinal uses are listed.